Visions of sugar plums - Evanovich, Janet (New York : St. Martin's Press, 2002)
Just before Christmas, a tall, long-haired blond in boots and jeans materializes in Stephanie's kitchen. Really -- the door and windows are locked. He says his name is Diesel, and he needs Stephanie's help to find someone.
"A Stephanie Plum holiday novel"--Jacket.
Accelerated Reader AR
Keywords: Plum, Stephanie (Fictitious character) -- Fiction; Women private investigators -- New Jersey -- Fiction; New Jersey -- Fiction; Christmas stories